Students’ Perception of Using Whatsapp in Blended Learning on Reading - Liya Astarilla Dede Warman (UIR Press, 2018)
This research aimed to investigate students’ perception of using Whatsapp in blended learning on reading comprehension. This was a descriptive research. The participants of this study consisted of 40 students of the second semester at STMIK-AMIK Riau, Pekanbaru, Indonesia. The data collected through questionnaire and interview. The finding of this research showed that majority of the participants had positive perception towards the using Whatsapp in blended learning on reading comprehension. All of the means of students responses in the questionnaire in each items were at 3.5-4.5 which indicated students’ responses were positive or at high level. The result from questionnaire also revealed that students agreed that using whatsapp in blended learning on reading comprehension was useful, helpful and effective in learning English anytime and anywhere. The findings from interview results also revealed that there were positive aspects and drawbacks of using Whatsapp in blended learning on reading comprehension. Nevertheless, the positive aspects of using Whatsapp in blended learning on reading comprehension gave more benefits to the students’ learning activities and their performances. These benefits could be continued to students’ learning outcome especially on their reading comprehension ability.